Respuesta :

What is 2(m+1)=3(m-12)
The answer is M=38

answer m=38

2(+1)=3(−12)

Distribute

2(+1)=3(−12) ={2(m+1)}}=3(m-12)

2+2=3(−12)

Distribute

2+2=3(−12)2m+2={3(m-12)}}

2+2=3−36

subtract 2 from both sides of the equation

2 + 2 = 3 − 3 6

2m+2=3m-36 2 + 2 − 2 = 3 − 3 6 − 2

2m+2{-2}}=3m-36{-2}}

Simplify

subtract the numbers

2m+2-2=3m-36-2

2m=3m-36-2

subtract the numbers

2m=3m-36-2

2m=3m-38

Subtract  3   from both sides of the equation

2 = 3 − 3 8

2m=-3m=3 − 3 = 3 − 3 8 − 3m

ACCESS MORE